Charge transport through extended molecular wires with strongly correlated electrons. Issue 33 (26th July 2021) - Thomas, James O.; Sowa, Jakub K.; Limburg, Bart; Bian, Xinya; Evangeli, Charalambos; Swett, Jacob L.; Tewari, Sumit; Baugh, Jonathan; Schatz, George C.; Briggs, G. Andrew D.; Anderson, Harry L.; Mol, Jan A.
Abstract : Experimental studies of electron transport through an edge-fused porphyrin oligomer in a graphene junction are interpreted within a Hubbard dimer framework. Abstract : Electron–electron interactions are at the heart of chemistry and understanding how to control them is crucial for the development of molecular-scale electronic devices. Here, we investigate single-electron tunneling through a redox-active edge-fused porphyrin trimer and demonstrate that its transport behavior is well described by the Hubbard dimer model, providing insights into the role of electron–electron interactions in charge transport. In particular, we empirically determine the molecule's on-site and inter-site electron–electron repulsion energies, which are in good agreement with density functional calculations, and establish the molecular electronic structure within various oxidation states. The gate-dependent rectification behavior confirms the selection rules and state degeneracies deduced from the Hubbard model. We demonstrate that current flow through the molecule is governed by a non-trivial set of vibrationally coupled electronic transitions between various many-body ground and excited states, and experimentally confirm the importance of electron–electron interactions in single-molecule devices.